Diminished Tubule Epithelial Farnesoid X Receptor Expression Exacerbates Inflammation and Fibrosis Response in Aged Rat Kidney. Issue 1 (22nd July 2022) - Ha, Sugyeong; Yang, Yejin; Won Kim, Jeong; Son, Minjung; Kim, Doyeon; Kim, Mi-Jeong; Im, Dong-Soon; Young Chung, Hae; Chung, Ki Wung
Abstract: The age-associated functional decline of the kidney is accompanied by structural changes including glomerular sclerosis and interstitial fibrosis. Aging kidneys also exhibit increased vulnerability in stressful environmental conditions. In this study, we assessed the differences in responses between young and aged animals to folic acid (FA)-induced renal fibrosis. To monitor the effects of aging on FA-induced kidney fibrosis, we administered FA (250 mg/kg) to young (6-month old) and aged (20-month old) rats. The development of severe fibrosis was only detected in aged rat kidneys, which was accompanied by increased kidney injury and inflammation. Furthermore, we found that FA-treated aged rats had significantly lower farnesoid X receptor (FXR) expression in the tubular epithelial cells than the rats not treated with FA. Interestingly, the extent of inflammation was severe in the kidneys of aged rat, where the FXR expression was low. To explore the role of FXR in kidney inflammation, in vitro studies were performed using NRK52E kidney tubule epithelial cells. NF-κB activation by lipopolysaccharide treatment induces chemokine production in NRK52E cells. The activation of FXR by obeticholic acid significantly reduced the transcriptional activity of NF-κB and chemokine production. In contrast, FXR knockdown increased LPS-induced chemokine production in NRK52E cells. Finally, FXR-knockout mice that were administered FA showed increased inflammation and severe fibrosis. In summary, we demonstrated that diminished FXR expression in the epithelial cells of the renal tubules exacerbated the fibrotic response in aged rat kidneys by upregulating pro-inflammatory NF-κB activation.